Process Technology : an Introduction. - Haan, André B. de (De Gruyter textbook., 2015)
This book provides a general overview about chemical and biochemical process technology. It focuses on the structure and development of production processes, main technological operations and some important aspects of process economics. For the technological operations the author emphasis operating principles, reasons for application and available industrial equipment.